A practical synthesis of three aliphatic metabolites of capsaicin: 16-Hydroxycapsaicin, 17-hydroxycapsaicin, and 16, 17-dehydrocapsaicin. Issue 11 (3rd June 2023) - Li, Die; Guo, Lulu; Guo, Xiaodong; Mao, Jian; Liu, Fuqiang; Chai, Guobi; Shi, Qingzhao; Ji, Lingbo; Wang, Dingzhong; Zhang, Qidong; Fan, Wu
Abstract: The first straightforward synthesis of 16-hydroxycapsaicin, 17-hydroxycapsaicin and 16, 17-dehydrocapsaicin, the major aliphatic metabolites of capsaicin, is reported. The amidation of hept-6-enoic acid with vanillylamine hydrochloride, followed by olefin metathesis using 2-methylbut-3-en-2-ol as partner furnished 16-hydroxycapsaicin in 56.1% overall yield with excellent E -selectivity. The E -selective olefin metathesis of methyl hept-6-enoate with but-3-en-2-one led to α, β-unsaturated ketone compound, which was subject to Wittig reaction with Ph3 P + MeBr -, providing the corresponding 1, 3-diene derivative. After removing methyl group by hydrolysis and introducing hydroxyl group by hydroboration-oxidation, such diene could be further converted to 16, 17-dehydrocapsaicin and 17-hydroxycapsaicin with overall yields of 35.6 and 7.8%, respectively. GRAPHICAL ABSTRACT: UF0001